2020
DOI: 10.1111/epi.16437
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of hepatic cirrhosis may trigger admission for epilepsy and status epilepticus

Abstract: Objective To determine whether acute exacerbations of cirrhotic liver disease are associated with higher odds of readmission for epilepsy or status epilepticus. Methods The New York State Inpatient Database is a statewide dataset containing data on 97% of hospitalizations for New York State. In this retrospective, case‐crossover design study, we used International Classification of Diseases, Ninth Revision, Clinical Modification codes to identify index status epilepticus and epilepsy admissions. The primary ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A high level of clinical suspicion is required to identify NCSE that is associated with elevated mortality [ 5 ] . Gursky et al showed that HE events were associated with subsequent admissions for epilepsy or SE [ 14 ] . This effect was even higher for admission with SE, with a three- to fivefold likelihood of admission with SE in the next 6 months [ 14 ] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high level of clinical suspicion is required to identify NCSE that is associated with elevated mortality [ 5 ] . Gursky et al showed that HE events were associated with subsequent admissions for epilepsy or SE [ 14 ] . This effect was even higher for admission with SE, with a three- to fivefold likelihood of admission with SE in the next 6 months [ 14 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Gursky et al showed that HE events were associated with subsequent admissions for epilepsy or SE [14] . This effect was even higher for admission with SE, with a three-to fivefold likelihood of admission with SE in the next 6 months [14] . Table 1 summarizes the four case reports found in PubMed, CINAHL and Web of Science [15][16][17][18] .…”
Section: Figure 1 Case 1: Eeg Showing Status Epilepticusmentioning
confidence: 99%